(untitled) (Asian Journal of Social Science Studies, 2018)
The purpose of this study is to explore Vietnamese women’s responses to domestic violence in South Korea. Based on in-depth interviews with 22 Vietnamese women who marry Korean men, six strategies to cope with domestic violence are identified: enduring, escaping, confronting, negotiating, getting help from informal networks, and seeking assistance from formal sources. This study presents that informal social networks are critical in the process of help seeking for abused Vietnamese women.